Prevalence of Plasmodium falciparum parasites resistant to sulfadoxine/pyrimethamine in the Democratic Republic of the Congo: emergence of highly resistant pfdhfr/pfdhps alleles. (23rd July 2018) - Nkoli Mandoko, Papy; Rouvier, Florent; Matendo Kakina, Lebon; Moke Mbongi, Destin; Latour, Christine; Losimba Likwela, Joris; Ngoyi Mumba, Dieudonné; Bi Shamamba, Stomy Karhemere; Tamfum Muyembe, Jean-Jacques; Muepu Tshilolo, Léon; Parzy, Daniel; Sinou, Véronique
Abstract: Background: In 2005, the Democratic Republic of the Congo (DRC) switched to artesunate/amodiaquine as the first-line antimalarial in response to increasing sulfadoxine/pyrimethamine resistance and adopted intermittent preventive treatment using sulfadoxine/pyrimethamine in pregnancy. Objectives: To determine the prevalence of molecular markers of sulfadoxine/pyrimethamine resistance in southwestern DRC 10 years after the new policy was instituted. Methods: From March 2014 to December 2015, blood samples were collected from symptomatic patients presenting to outpatient centres in urban and rural areas. A total of 2030 confirmed Plasmodium falciparum isolates were genotyped at codons associated with sulfadoxine/pyrimethamine resistance. Results: The prevalence of pfdhfr -N51I, C59R and S108N and pfdhps -A437G mutations was consistently high; the prevalence of the pfdhps -K540E mutation was low but increased since its first report in 2008 in the same region, reaching 17.6% by 2015. The pfdhps -A581G mutation increased from ∼4.5% in 2014 to ∼14.0% in 2015 at urban sites while in rural areas it remained low (∼4.0%). The mutations pfdhfr -I164L and pfdhps -A613S were detected for the first time in DRC. Also, 11 (0.8%) isolates revealed the presence of the newly described pfdhps -I431V mutation. Combining pfdhfr and pfdhps alleles, quintuple and sextuple mutations were observed, with the emergence of septuple (IRNI/IAGEGA)- and octuple (IRNI/VAGKGS)-mutant genotypes. Conclusions: Intermittent preventive treatment using sulfadoxine/pyrimethamine during pregnancy remains warranted in southwestern DRC. However, the expansion of pfdhps -K540E mutation and emergence of mutants that cause higher levels of sulfadoxine/pyrimethamine resistance is concerning and may present a challenge for future preventive interventions in the country.